China Dominates Asia-Africa Trade Market and Enters America - Siregar, Tonggong (Sultan Agung Notary Law Review, 2025)
China has developed into a global economic power that dominates trade markets in Asia and Africa and seeks to expand its influence in the Americas. This article discusses China's expansion strategy in Asia, its economic dominance in Africa, its efforts to penetrate the American market, and the impact of the China-US trade war on Indonesia. In Asia, China is using the Belt and Road Initiative (BRI) to strengthen trade and infrastructure ties, creating economic dependence on countries in the region. Large investments in the technology, manufacturing, and logistics sectors have made China a major trading partner for Asian countries, including Indonesia. In Africa, China has consolidated its dominance through large investments in infrastructure, mining, and energy projects. Soft loan policies and development projects have increased the economic dependence of African countries on China, despite concerns about excessive debt. In the Americas, China faces major challenges due to protectionist policies and the trade war led by the United States. Nevertheless, China continues to try to enter the American market through investments in the technology, automotive, and property sectors, as well as through indirect trade strategies by utilizing third countries as export routes. The trade war between China and the United States has had a significant impact on Indonesia. As a country that has trade relations with both countries, Indonesia experiences commodity price fluctuations, increased investment from China, and economic uncertainty due to geopolitical tensions. However, this situation also opens up opportunities for Indonesia to fill the market gap left by trade restrictions between the two superpowers. Through this study, it can be concluded that China's economic expansion has had a major impact on the structure of global trade. Indonesia needs to navigate these dynamics with adaptive policies to take advantage of opportunities while mitigating the risks that arise from economic competition between China and America.